2007
DOI: 10.1111/j.1471-6402.2007.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Roles of Race and Gender-Role Attitudes in the Relationship Between Sexual Harassment and Psychological Well-Being

Abstract: Although previous research has linked sexual harassment to negative psychological outcomes, few studies have focused on moderators of these relationships. The present study surveyed Black (n= 88) and White (n= 170) female undergraduates who endorsed experiences of sexual harassment to examine whether traditional gender attitudes differentially moderated the relationship between sexual harassment and three outcomes: posttraumatic stress symptoms, general clinical symptoms, and satisfaction with life. We replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 69 publications
(91 reference statements)
3
23
1
Order By: Relevance
“…Although race predicted psychological distress, results indicated that White women reported more psychological distress than Black women, counter to our prediction that Black women's increased vulnerability would exacerbate their distress once harassed. A similar pattern was reported among Black and White sexually harassed college students (Rederstorff, Buchanan, & Settles, 2007). These results may be related to cultural differences in the manifestation of psychological distress (Zhang & Snowden, 1999); specifically, past studies have found that White women more readily endorse symptoms of depression, whereas Black women are more likely to report symptoms of somatization (Franko et al, 2005).…”
Section: Discussionsupporting
confidence: 83%
“…Although race predicted psychological distress, results indicated that White women reported more psychological distress than Black women, counter to our prediction that Black women's increased vulnerability would exacerbate their distress once harassed. A similar pattern was reported among Black and White sexually harassed college students (Rederstorff, Buchanan, & Settles, 2007). These results may be related to cultural differences in the manifestation of psychological distress (Zhang & Snowden, 1999); specifically, past studies have found that White women more readily endorse symptoms of depression, whereas Black women are more likely to report symptoms of somatization (Franko et al, 2005).…”
Section: Discussionsupporting
confidence: 83%
“…Whereas much evidence exists to support a discrimination–distress link, less is known about the relationship between discrimination and psychological well‐being. Some evidence suggests negative associations, such as those observed in samples of African American and European American women (Rederstorff, Buchanan, & Settles, 2007; Ryff, Keyes, & Hughes, 2003), Asian Americans (Lee, 2003), and African American adolescents (Sellers, Copeland‐Linder, Martin, & Lewis, 2006). Therefore, we thought it important to explore potential mediating processes in sexist events’ association with distress as related to, but distinct from, mediating processes in their relationship with psychological well‐being.…”
Section: A Broader Conceptualization Of Mental Health: Psychological mentioning
confidence: 99%
“…For women who are members of multiple marginalized groups, it may be difficult—or impossible—to tease out the origins of discriminatory events as reflecting primarily sexism, other prejudices, or interactions among multiple prejudices. These experiences could result in lower levels of PBJW and PC among Women of Color as compared to European American women, and some data suggest that sexist discrimination is experienced differently by these two broad groups (Rederstorff et al, 2007). For these reasons, we also examined our data for possible differences by self‐reported ethnic identity by comparing data from Women of Color and European American women in three ways: by testing for differences in mean responses, by testing for differences in intercorrelations among variables, and by including ethnic identity status in the sequential path model.…”
Section: Additional Sources Of Variance: Impression Management and Etmentioning
confidence: 99%
“…For example, although both Black and White women may experience sexual harassment, Black women are more likely to experience sexual harassment that has a racial component (racialized sexual harassment; Buchanan, 2005; Buchanan & Ormerod, 2002). Another example of intersectionality is the finding that feminist attitudes buffered psychological outcomes for sexually harassed White women, but exacerbated psychological outcomes for sexually harassed Black women (Rederstorff et al, 2007). Thus, we regard gender and race as often internalized group memberships (i.e., identities) that intersect in many ways; one way is that women's racial group membership creates a unique lens that informs how their gender is viewed.…”
Section: Conceptualizations Of Gender and Racementioning
confidence: 99%